1974
DOI: 10.2134/agronj1974.00021962006600050016x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Between and Within‐Row Spacing on Agronomic Characteristics of Irrigated Soybeans1

Abstract: Several workers have reported on the effect of varying between and within‐row spacing on soybean (Glycine max (L.) Merr.) yield but few have used irrigated soybeans. We studied two row‐widths, and two in‐row spacings in a split‐split plot arrangement in 1969 and 1970 using five soybean cultivars on irrigated plots. Plants in '46‐cm row width or 3.8‐cm within‐row spacing were taller, lodged more, and produced fewer nodes, branches, pods on branches, pods on main stem, and total seeds on a per plant basis. Heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Basnet et al . (4) found that in narrow rows the first pods were produced 3 to 9 cm higher above ground level than those in wider soybean row spacings.…”
Section: Row Spacingmentioning
confidence: 89%
See 1 more Smart Citation
“…Basnet et al . (4) found that in narrow rows the first pods were produced 3 to 9 cm higher above ground level than those in wider soybean row spacings.…”
Section: Row Spacingmentioning
confidence: 89%
“…One disadvantage is that soybeans planted in narrow rows tend to be lodged more than wide row soybeans (4,19,66). Hartwig (43) states that planting more than 10 to 12 soybean seeds per 0.3 m of row gives better early season weed control but a greater amount of loding usually results.…”
Section: Row Spacingmentioning
confidence: 99%
“…He observed that thick plantings are conducive to lodging and delayed maturity, but the highest yields were with the 4-cm spacing. Subsequent research has focussed on yield characteristics of several varieties under different agronomic conditions (Basnet et al, 1974;Cordonnier and Johnston, 1983;Dose and Thurlow, 1974;Lehman and Lambert, 1960;Munoz et al, 1983). Thus, we postulated the increase in net canopy photosynthesis which occurs at high density compared to low density planting should result in an increased dinitrogen fixation rate and higher yields without a decrease in nutritional quality of the beans.…”
Section: Introductionmentioning
confidence: 96%
“…Increase in density has not a significant effect on yield by means of regulating distances and in some cases leads to decrease in yield. As reducing the density, the number of pods per minor and main branches and the number of grain per plant, seed weight are increased but the density has no any effect on 1000-kernel weight 19 .…”
mentioning
confidence: 95%